Detecting income-smoothing behaviors of Turkish listed companies through empirical tests using discretionary accounting changes - ATİK YILDIRIM, ASUMAN (My University, 2009)
Flexibility when selecting accounting methods sometimes motivates managers to choose accounting methods or to change employed ones in order to increase, decrease or smooth income figures. In this study, income-smoothing behaviors of Turkish listed companies are detected through empirical tests using discretionary accounting changes (DACs). Parallel to the study conducted by Moses [Moses OD. Income smoothing and incentives: empirical tests using accounting changes. The Accounting Review 1987;11(2):358-77], income smoothing is accepted as one motivation of DACs and the sample firms are classified as smoothers and non-smoothers by using Moses' smoothing behavior index. Results show that possible motivations of DACs are income smoothing, economical characteristics of the periods in which the DACs are made, and the desire of Turkish firms to have net incomes close to zero. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Discretionary accounting changes; Income smoothing; Istanbul Stock Exchange; Moses model